Design and Construction of a Web-Based Machine Ordering Application Using the Codeigniter Framework - Bebi Rahmawati; Siti Fauziyah; Siti Iis Istianah; Anas Fadhlulloh; Alwan Mukhlisinardi (Journal Collabits, 2025)
The company PT Engineering is engaged in manufacturing machinery and machine tools, repairing metal products, and repairing electrical equipment. The company was founded with the aim of meeting the needs of the industry in terms of providing high-quality equipment. the process of ordering production machines, such as tanks and mixers, which is currently running is still carried out using whatsapp or email media, so it is less effective and can cause various problems such as data recording errors, and less optimal service to customers. The absence of an integrated ordering system also makes it difficult for companies to track order status so that they cannot provide fast and accurate information to customers. The purpose of this research is to facilitate the production department and planner to monitor incoming orders so that orders can be completed on time. This research uses RAD analysis research method, diagram design using UML, system coding using PHP programming language and Mysql database. This research produces a web-based ordering system that is connected to a database so that order data can be stored properly.